Design and Validation of a Rubric for the Evaluation of Digital Competencies based on Socioformation - Salazar Gómez, Elizabeth (2018)
Due to the lack of research and tools that explore and evaluate digital competencies, both in educational and community contexts, a rubric of evaluation in digital competencies from a socio-formative approach was designed consisting of: 1) Literature review of existing documents to diagnose or evaluate digital competencies; 2) construction of the instrument through a rubric type structure with the socio-formative taxonomy; 3) review and improvement of the instrument by a panel of 3 experts; 4) the content was validated by a panel of 14 expert judges; 5) the application of the instrument to a pilot group, composed of 45 persons; 6) final improvement of the instrument based on the suggestions and evaluations of the expert judges. Results: from the results of the evaluation by expert judges, an analysis of the descriptive data was carried out, and, according to the Aiken’s V coefficient, items 4,5,6 and 7 obtained a score of (V>0.80), but it was different for items 1,2 and 3, which reflected a lower score (V<0.80). From this and the suggestions issued by the expertjudges, the instrument was modified in relevance and drafting; as for the reliability level according to the value of Cronbach ́s Alfa it situated at .845; suggesting that the instrument is reliable. As for qualitative evaluation, a frequency within acceptable levels was obtained with high relevance and redaction, suggesting improvements in the questions, but there was no suggestions about the elimination of items.